Relationship of breast arterial calcification and radiotherapy - Karataş, Gökhan; Kula, Osman; Tunçbilek, Nermin (The European Research Journal, 2024)
Objective: The purpose of this research is to compare the pre and post-radiotherapy mammograms of patients who had breast-conserving surgery (BCS) and radiotherapy to see how radiotherapy affects breast arterial calcifications (BAC). Methods: The study retrospectively compared the mammography examinations at least 24 months after radiotherapy and pre-radiotherapy mammography examinations of 123 female patients diagnosed with breast cancer and treated with BCS and radiotherapy between December 2001 and July 2011. Results: Breast arterial calcifications (BAC) increased statistically significantly in 25 patients who underwent radiotherapy after BCS. Conclusion: Our results indicate that BAC increases significantly after RT, especially in breasts treated with radiotherapy, with age being also a risk factor for BAC development.